Dickkopf-3, a Tissue-Derived Modulator of Local T-Cell Responses - Meister, Michael; Papatriantafyllou, Maria; Nordström, Viola; Kumar, Varun; Ludwig, Julia; Lui, Kathy O.; Boyd, Ashleigh S.; Popovic, Zoran V.; Fleming, Thomas Henry; Moldenhauer, Gerhard; Nawroth, Peter P.; Gröne, Hermann-Josef; et al. (Frontiers in Immunology, 2015)
The adaptive immune system protects organisms from harmful environmental insults. In parallel, regulatory mechanisms control immune responses in order to assure preservation of organ integrity. Yet, molecules involved in the control of T cell responses in peripheral tissues are poorly characterized. Here, we investigated the function of Dickkopf-3 in the modulation of local T cell reactivity. Dkk3 is a secreted, mainly tissue derived protein with highest expression in organs considered as immune privileged such as the eye, embryo, placenta and brain. While T cell development and activation status in naïve Dkk3 deficient mice was comparable to littermate controls, we found that Dkk3 contributes to the immunosuppressive microenvironment that protects transplanted, class-I mismatched embryoid bodies from T cell mediated rejection. Moreover, genetic deletion or antibody mediated neutralization of Dkk3 led to an exacerbated experimental autoimmune encephalomyelitis (EAE). This phenotype was accompanied by a change of T cell polarization displayed by an increase of IFNγ producing T cells within in the CNS. In the wild type situation, Dkk3 expression in the brain was up-regulated during the course of EAE in an IFNγ dependent manner. In turn, Dkk3 decreased IFNγ activity and served as part of a negative feedback mechanism. Thus, our findings suggest that Dkk3 functions as a tissue-derived modulator of local CD4+ and CD8+ T cell responses.